The endogeneity of optimum currency areas criteria: some evidence from the European Union and Portugal - Silvestre, João (2007)
Observing the statistical relationship between business cycles correlation and trade intensity in the European Union, euro zone, and the Portuguese economy, we conclude that there is, in general, a positive effect that supports the endogeneity argument proposed by Frankel and Rose (The Economic Journal 108(449):pp. 1009–1025, 1998). However, if we analyse this relationship in sub-periods – 1967–1975, 1976–1985, 1986–1992, and 1993–2003 – we conclude that endogeneity hypothesis just hold in the first two, although the correlations are increasing. This could mean that, after the Single European Act in 1986, other forces beyond trade are contributing to business cycle synchronization. The Portuguese business cycle correlation with the European Union and the Euro zone had also increased in these four decades, despite the fact that endogeneity hypothesis is at a 90 percent confidence level. We also analyse the bilateral relationships between the Portuguese economy and the other European Union countries and find that the endogeneity is confirmed in just four cases: Spain, Ireland, Netherlands, and UK.